Comparaison du Plexisol® P550 et du Medium de Consolidation® 4176 - Guillemette Lardet (CeROArt : Conservation, Exposition, Restauration d'Objets d'Art)
In order to consolidate pictorial layers, synthetic resins are used for impregnation of the original medium. With the diversification of products designated to paintings restoration, habits must not prevent the use of new materials that could be more adapted. The Lascaux 4176 Medium for Consolidation® is here compared to Plexisol® P550 in operations of impregnation of paintings, by the measurement of several parameters such as: the capacity of penetration, the stickiness and the elasticity of adhesive films.